CRESCIMENTO RELATIVO DE Callinectes ornatus Ordway, 1863 (CRUSTACEA, DECAPODA, PORTUNIDAE) NA BACIA POTIGUAR- RN - Silva, Edenice dos Santos; Alves, Sheila Maria da Silva; Albuquerque, Douglas Everton Silva de; Bispo, Milton Cesar; Albuquerque, Débora Lucatelli de; Araújo, Marina de Sá Leitão Câmara de (Revista Nordestina de Zoologia, 2016)
This paper aims a comparative analysis about the growth relative individuals of the species Callinectes ornatus Ordway, 1863 coming Potiguar Basin - RN. Callinectes ornatus Ordway, 1863, known as "blue crab", tolerates wide variation of salinity, inhabiting since the outfall rivers to the ocean to 75 meters deep. This species presents eating habits carnivorous opportunistic, feeding is debris, which represents an important role in marine environment. The material examined was collected by Petrobras and donated to the “Coleção Didática de Zoologia” (CDZ / UPE) of the University of Pernambuco, Campus Garanhuns. Were analyzed 166 individuals of which 107 males and 53 females. Among females four are ovigerous, and 6 juvenile whose sex unable to distinguish. The sex ratio was diverted in favor of males (χ² = 18.23, 1♀: 2.02♂). The width of the carapace (WC), average of males was 52,70; ± 13,40 mm, while in females 45,27 ± 15,41 mm. This value was significantly lower than that of males (p <0,05). The average carapace length (CL) was 26,42 mm ± of 9,82 in females. In males the CL was 30,64 ± of 8,29 mm. Males were significantly higher than females. In the females the abdomen width (AW) was 16,20 ± 7,34 mm. The chelipod length in males was 32,18 ± 10,85 mm. The average total weight of males was 19,2 g ± 14,1g. In females 12,9 g ± 14,6 g, being the value concerning females significantly lower than that of males (p<0,05). The results showed that males were higher and heavier than females, corroborating, therefore, with previous studies. This feature is an important adaptation to copulation because males largest have greater ease in the manipulation of females.